Microbial contamination of drinking water from water coolers in Universiti Putra Malaysia residential colleges - Yusof, Khairi Haziq; Mohd Sham, Shaharuddin; Awang Hamat, Rukman (Malaysian Medical Association, 2015)
Introduction: Water coolers are popular in office buildings and commercial stores. This source of drinking water has the potential to cause waterborne outbreaks, especially in sensitive and immuno-compromised subjects. The main reason for this research was because the majority of students preferred to consume water from water coolers due to factors such as convenience and accessibility.